Techno-economic evaluation of the Portuguese PV and energy storage residential applications - Foles, Ana (2021)
In the residential sector, energy micro-generation and its intelligent management have been creating novel energy market models, considering new concepts of energy usage and distribution, in which the prosumer has an active role in the energy generation and its self-consumption. The configuration of a solar photovoltaic system integrating energy storage in Portugal is yet unclear in the technical, energetic and economic point of view. The energy management jointly with the battery operation have great influence in the system configuration’s profitability value. The present work evaluates different photovoltaic system configurations with and without batteries for the normal low voltage Portuguese consumer profile with 3.45 kVA contracted power. This study presents the systems’ cost-effectiveness, within the Portuguese legislation, which promotes and enables policies for self-generation and self-consumption. The analysis is done in three different representative locations of the country, considering distinct electric tariffs. This work shows that despite the solar photovoltaic system without electricity storage is already economically viable, its integration with storage is not in most of the assessed configurations. However, it is shown that it is already possible to find profitable PV + battery configurations, even potentially improving these positive scenarios if a good energy management strategy is considered.